Precise multispecies agricultural gas flux determined using broadband open-path dual-comb spectroscopy - Herman, Daniel I.; Weerasekara, Chinthaka; Hutcherson, Lindsay C.; Giorgetta, Fabrizio R.; Cossel, Kevin C.; Waxman, Eleanor M.; Colacion, Gabriel M.; Newbury, Nathan R.; Welch, Stephen M.; DePaola, Brett D.; Coddington, Ian; Santos, Eduardo A.; et al. (My University, 2021)
Advances in spectroscopy have the potential to improve our understanding of agricultural processes and associated trace gas emissions. We implement field-deployed, open-path dual-comb spectroscopy (DCS) for precise multispecies emissions estimation from livestock. With broad atmospheric dual-comb spectra, we interrogate upwind and downwind paths from pens containing approximately 300 head of cattle, providing time-resolved concentration enhancements and fluxes of CH4, NH3, CO2, and H2O. The methane fluxes determined from DCS data and fluxes obtained with a colocated closed-path cavity ring-down spectroscopy gas analyzer agree to within 6%. The NH3 concentration retrievals have sensitivity of 10 parts per billion and yield corresponding NH3 fluxes with a statistical precision of 8% and low systematic uncertainty. Open-path DCS offers accurate multispecies agricultural gas flux quantification without external calibration and is easily extended to larger agricultural systems where point-sampling-based approaches are insufficient, presenting opportunities for field-scale biogeochemical studies and ecological monitoring.